Moderasi Beragama sebagai Landasan Etika Ekonomi dalam Praktik Pemberdayaan Masyarakat Berkelanjutan: Studi Kasus Desa Bintang Meriah - Fauziah Nasution; Alyyatul Nisa Ragil Lesmana; Nabilah Irwani; Shafa Sizli Kania (Jurnal Pengabdian Masyarakat Waradin, 2026)
This study examines the role of religious moderation as an ethical foundation for economic practices in sustainable community empowerment in Bintang Meriah Village. The research employs a descriptive qualitative approach with a participatory model through the Community Service Program (KKN) of the State Islamic University of North Sumatra. The values of religious moderation were integrated into various social, economic, and environmental programs, including anti-bullying campaigns, Islamic financial literacy, eco-print training, and the use of papaya leaf extract as an organic pesticide. Religious moderation serves as an ethical basis for fostering tolerance, social responsibility, and economic balance, while eco-theology strengthens ecological awareness and sustainability. The findings indicate an increase in community awareness of the importance of ethical and spiritual values in economic and environmental activities. The synergy between students, the community, and local government created empowerment practices that are not only economically beneficial but also uphold spiritual values and social sustainability.